Deciphering the record of hyaenic activity in the Early Pleistocene site of Fuente Nueva-3 (Baza Basin, SE Spain) - Espigares-Ortiz, María Patrocinio; Palmqvist-Barrena, Carlos Paul; Ros-Montoya, Sergio; Rodríguez-Ruiz, María Dolores; Pérez-Ramos, Alejandro; Guerra-Merchán, Antonio; Granados, Alejandro; Rodríguez-Gómez, Guillermo; García-Aguilar, José Manuel; Martínez-Navarro, Bienvenido (My University, 2022)
FN3 is an open air site, dated ~1.4 Ma. Their archaeological levels preserve evidences of human presence, consisting in lithic artefacts and cuts and percussion marks on bones. The lithic remains are associated with abundant macromammals bones with a very wide size range, from proboscideans to small mustelids. Carnivores are represented, mainly, by isolated teeth, bellowing to canids, ursids, felids and hyaenids, and their activity is recorded by the presence of different tooth marks types. However, there exists an important difference in the carnivore record between the levels, consisting in the presence of more than 200 coprolites in the Upper Level, whereas in the Lower Level these elements are practically absent. For the identification of the defecating organism, different analyses have been performed. The morphological study evidences the presence of the seven shape-types of pellets, although the most common morphologies are round, oval and disk. The colour of hyena faeces is also very characteristic, colour analysis of FN3 coprolites shows a predominance of whitish and very pale brown tonalities. To determine the composition, the samples were studied by XRD, XRF and SEM. The results have revealed that the coprolites mostly consist of calcium phosphate. These data are consistent with the expected composition of faeces in an organism that ingests a large amount of bones, in addition, macroscopic observation of the coprolites surface evidence the presence of numerous fragments of digested bones within them. All these features allow us to adscribe the FN3 coprolites to the hyaena Pachycrocuta brevirostris, species of which several teeth have been found at this site.This record manifests a great difference between both archaeological levels, showing in the Upper Level a scenario were hominin and hyaenids coexisted and competed for food resources, whereas in the Lower Level hyaenas were practically absent, and the main modifying agent was early Homo.
Keywords: Tafonomía; Paleontología; Pleistoceno; Baza (Granada); Yacimientos paleontológicos; Early Pleistocene; Coprolites; Fuente Nueva-3 (Yacimiento, Granada); Pachycrocuta